On the Classification of the Annelides [Translated by W. S. Dallas] - Quatrefages, Armand de (Annals and Magazine of Natural History, 1866)
None. Begins: "All naturalists know what Linnaeus and his immediate successors understood by the word Vermes; they also know that Cuvier was the first to disentangle the chaos in which the want of precise knowledge had long left this mass of Invertebrata, and that in consequence of the division of the animal kingdom into four sections (embranchements), the expression Vermes ceased for a long time to be applied to any group of the animals of which it had formerly been the common designation
World Polychaeta Database (WPolyDb) Kristian Fauchald's Polychaeta DB